Effect of Heat Treatment on Color Change and The Physical Properties of Sembilang Bamboo (Dendrocalamus giganteus Munro) - Nurhanifah; Siska Anggiriani; Jajang Sutiawan (Journal of Sylva Indonesiana, 2024)
Timber as a raw material for making furniture is still lacking. One alternative to overcome this problem is bamboo. The potential for bamboo in Indonesia is quite large. Sembilang bamboo is a species of bamboo that has not been widely used. Research related to the effect of heat treatment on color change and the physical properties of bamboo needs to be carried out to determine color change and the dimensional stability of bamboo. This research was carried out by giving heat at 180°C for various durations (control, 3 hours, and 6 hours). The color change, moisture content, absorption, and specific gravity of heat-treated sembilang bamboo were researched. The results showed that the color of sembilang bamboo after heat treatment became darker than the control. The moisture content and absorption values of sembilang bamboo with heat treatment at 180°C for 6 hours were higher than the control and 3 hours. The specific gravity value of the bamboo control was higher than 3 hours and 6 hours for sembilang bamboo. Heat treatment at 180°C for 6 hours had an adverse effect on the physical properties of sembilang bamboo. Heat-treated sembilang bamboo at 180°C for 3 hours was recommended in this research